Performance of salinity tolerance of F3 rice lines of BRRI dhan 29 × PBRC (STL-20) using RAPD markers - Mazumder, Nazmul Islam; Sultana, Tania; Paul, Prtitish Chandra; Roy, Dinesh Chandra; Sushmoy, Deboprio Roy; Haque, Md Shamiul; Razia, Sultana; Noor, Md Mahmud Al (Research in Agriculture Livestock and Fisheries, 2019)
Twenty six rice lines of PBRC (salt tolerant line-20) × BRRI dhan-29 were used to evaluate salinity tolerance at the seedling stage and tested for salt tolerance using RAPD markers. Salinity screening was done using hydrophonic system at the greenhouse following IRRI standard protocol. Among the studied line, ten were moderately salinity tolerant, nine susceptible and rest of the lines highly susceptible. For assessing genetic diversity and relationship of F3 rice lines including two parents were tested against PCR-based Random Amplified Polymorphic DNA (RAPD) technique using three arbitrary decamer primers; OPA02, OPC01, and OPC12. Selected three primers generated a total of 14 bands. Out of 14 bands, 12 bands (86.67%) were polymorphic and 2 bands (13.33%) were monomorphic. The Unweighted Pair Group Method of Arithmetic Means (UPGMA) dendrogram constructed from Nei’s (1972) genetic distance produced 2 main clusters of the 28 rice genotypes. Most of the moderately tolerant lines and PBRC (STL-20) (tolerant variety) were grouped in same cluster due to lower genetic distance, while maximum susceptible along with BRRI dhan29 (susceptible variety) showed higher genetic distance with PBRC (STL-20) and moderately tolerant lines. This result indicates that the lines which formed grouped together, they are less diversed. On the other hand the lines remain in different clusters or different groups, are much diversed. Thus RAPD perform a potentially simple, rapid and reliable method to evaluate genetic diversity and molecular characterization as well. Res. Agric., Livest. Fish.6(2): 215-225, August 2019